2010
DOI: 10.1021/ie101069w
|View full text |Cite
|
Sign up to set email alerts
|

Charge Carrier Transfer: A Neglected Process in Chemical Engineering

Abstract: This paper presents the discussion that charge carrier transfer should be treated by modern chemical engineering on equal terms with other transfer processes such as mass, heat, and momentum transfer. In an age when chemical engineering is entering the field of electronics, electrostatics, and electrochemistry, more and more often involving examination down to the molecular level, it is impossible to describe much phenomena without taking into consideration the charge carrier transfer. The discussion, the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
(191 reference statements)
0
4
0
Order By: Relevance
“…11 This generally results in a zero field mobility 2−3 orders of magnitude greater than systems which rely upon hopping transport. 40 With this in mind, the difference in zero field mobility of the F n BsubPcs (Figure 2) may be explained by their differences in solid state arrangements and, more specifically, the arrangement of their π-electron systems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 This generally results in a zero field mobility 2−3 orders of magnitude greater than systems which rely upon hopping transport. 40 With this in mind, the difference in zero field mobility of the F n BsubPcs (Figure 2) may be explained by their differences in solid state arrangements and, more specifically, the arrangement of their π-electron systems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been shown that molecules which pack in extended π-stacked or π-aligned arrays, and thus form a continuous pathway for electrical conduction, have high charge carrier mobilities in OTFTs . This generally results in a zero field mobility 2–3 orders of magnitude greater than systems which rely upon hopping transport . With this in mind, the difference in zero field mobility of the F n BsubPcs (Figure ) may be explained by their differences in solid state arrangements and, more specifically, the arrangement of their π-electron systems.…”
Section: Resultsmentioning
confidence: 99%
“…These "updates" to classical transport phenomena syllabuses are not exclusive to light transport: a couple of years ago, reviews and perspectives published in specialised literature urged that more studies be dedicated to basic transport phenomena that are likely to affect Chemical Engineering in ways that were not yet fully understood at that moment. One example is charge carrier transportation in solids 6,7 : electrons, vacancies; subatomic particles and crystal defects. From the Physics perspective, these phenomena might be reasonably well known; but the role they play in a chemical reaction, the scale of their importance, and how this knowledge can be used to improve existing equipment is yet to be fully pictured.…”
Section: Introductionmentioning
confidence: 99%
“…Different from c-TiO 2 , amorphous TiO 2 (a-TiO 2 ) may contribute some special characteristics to facilitate the utilization of visible and even near infrared light. Theoretically, the disordered arrangement of atoms in an amorphous semiconductor can contribute to the coexistence of localized and extended states, and the range between the conduction and valence bands becomes more and more narrow with increasing disorder as indicated by the Mott-CFO model; 10 thus, the mobility gap of an amorphous semiconductor, identical to the bandgap of a crystalline semiconductor, 11 can be narrowed by this characteristic. Based on this theory, a-TiO 2 , due to the superiority of its mobility gap, is able to harvest visible and even near infrared light without extra bandgap optimization, which simplifies its preparation, saves costs, and reduces pollutants.…”
Section: Introductionmentioning
confidence: 99%